Molecular Detection of Burkholderia cepacia and Comparative Study Between Medical Plant and Antibiotics against Bacteria Isolates from Cystic Fibrosis - Angham Najah Al-Khafaji; Mohammed Subhi Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: One of the major deaths causes in the patients with cystic fibrosis (CF) is the impaired lungfunction. Lately, Burkholderia cepacia was considered as a significant opportunistic pathogen in suchpatients. Since the late 1970s, due to its increased isolation from CF patients, its ability to spread infectionsin the community of CF patients, its role in disrupting lung function, and its inherent resistance to multipleantibiotics. Those various factors are making the Burkholderia cepacia isolation one of the significant tasksin cystic fibrosis health-care environment.Objective: To identify the method and the complete recA nucleotide sequence, and to compare the isolatedbacteria from CF by medicinal plants and antibiotics.Material and Methods: Bacterial identification of CF patients was carried out by standard microbiologicalmethods and identification was carried out using biochemical tests Vitek2 compact system, and PCRidentification to confirm the identification and evaluate the antibacterial activity in Mentha leaves and lemonpeel extracts against pathogenic bacteria.Results: Biochemical tests and gene expression confirmed that Burkholderia cepacia and Pseudomonas sppstrains were isolated from 50 sputum samples. These results indicate that Mentha leaves extract is better thanlemon peel extract, compares with antibiotics reveal the resistance of these bacteria.